Energy storage device

By setting a self-limited temperature conductive paste layer between the current collector and the active substance of the energy storage device, the temperature increase and safety problems when the internal short circuit of the energy storage device are solved, and the energy density, stability and cycling performance are improved. The effect is also provided with high temperature protection to prevent the battery from ignition and explosion.

CN119481070APending Publication Date: 2025-02-18GMCC ELECTRONICS TECH WUXI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980407.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

When existing energy storage devices are short-circuited internally, it is easy to cause local current density to increase, resulting in rapid increase in temperature, decomposition of positive and negative active substances and combustion of electrolytes, which may cause battery fire and explosion.

Method used

Multiple electrode sheets are used to assemble the battery cell in a stack assembly method of alternating current collector, active substance and separator, and a self-limiting conductive paste layer is provided between the current collector and the active substance, and the paste is polymerized. It is composed of substances and uniformly dispersed carbon dot particles, which can cut off current transmission when the temperature rises and provide overheating protection.

Benefits of technology

It effectively reduces the use of conductive carbon black, improves the energy density and stability of the pole sheet, reduces battery polarization and internal resistance, improves cycling performance, and provides safety protection in high-temperature environments to prevent battery fire and explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119481070A_ABST
    Figure CN119481070A_ABST
Patent Text Reader

Abstract

The invention discloses an energy storage device, and relates to the technical field of electrochemistry. Comprising a plurality of electrode plates, the electrode plates are assembled into a battery cell in a lamination assembly mode that current collectors, active substances and diaphragms are alternately arranged, the two current collectors on the outermost side are a total positive current collector and a total negative current collector respectively, and a negative active material layer and a positive active material layer are arranged on the inner side faces of the total positive current collector and the total negative current collector respectively. The internal cell pole piece comprises an internal current collector, a positive active material layer and a negative active material layer, and conductive slurry coatings are arranged between the two current collectors on the outer side and the positive active material layer and between the internal current collector and the negative active material layer respectively. According to the energy storage device provided by the invention, the chemical stability and thermal stability of the current collector are improved, and the energy storage device has high safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of electrochemical technology, and in particular to an energy storage device. Background Art

[0002] For commercial energy storage devices, once an internal short circuit occurs, the local current density increases, and the entire battery will discharge through the short circuit point, causing the dendrite growth tendency in these areas to be stronger. A large amount of energy is released through the short circuit point in a short period of time, causing the temperature to rise rapidly, leading to the decomposition of positive and negative active materials and the combustion of the electrolyte. In severe cases, the battery may catch fire and explode.

[0003] The reason is that when a short circuit occurs, since the positive and negative electrodes use aluminum and copper current collectors, the high electronic conductivity of the metal allows electrons to flow quickly and instantly. At the short-circuit point, the lithium ion flow immediately has a very large current density for the insertion and extraction of lithium ions. Taking the negative electrode graphite as an example, the extremely rapid release of lithium ions will cause lithium dendrite problems. For the positive electrode, there is no rapid ion transfer, which leads to the destruction of the crystal structure. All of the above will aggravate the failure of the battery cell itself, leading to thermal runaway and spontaneous combustion and explosion.

[0004] At the same time, the traditional conductive paste is directly coated on the surface of the aluminum foil, and after drying, the active material is adhered to the surface of the current collector through the binder. However, this has the following disadvantages: first, the conductive carbon material is a semiconductor, and its conductivity is worse than that of copper and aluminum pastes; second, the conductive carbon material has a large specific surface area, and the particles are not tightly stacked after drying; third, the binder only has a bonding function and does not have conductivity, which will weaken the conductive function to a certain extent. In addition, the traditional conductive paste does not have a temperature control function, that is, as the temperature rises, the resistance of the conductive carbon material tends to decrease, causing the device to overheat and cause safety problems.

[0005] The traditional processing method for positive and negative electrode sheets is to coat the slurry of positive and negative electrode active materials mixed with binders, conductive agents, and solvents on copper foil or aluminum foil. In the case of internal and external short circuits, the copper foil and aluminum foil of the electrode sheets prepared by the traditional processing method act as wires, the positive and negative electrodes are continuously connected, and the temperature of the device rises sharply, which can easily cause the device to rupture or explode. In order to solve the above problems, PTC (positive temperature coefficient) elements are generally installed in energy storage devices, but their response speed is slow, resulting in a temperature response lag. The maximum current and maximum voltage they can withstand are limited, and they cannot sensitively sense changes in the internal temperature of the device, nor can they respond to positive and negative short circuits.

[0006] Based on this, a new technical solution is needed to provide an energy storage device with low cost, easy preparation and high safety factor. Summary of the invention

[0007] The purpose of the present invention is to provide an energy storage device to solve the above problems in the prior art.

[0008] In order to solve the above-mentioned problem, according to one aspect of the present invention, there is provided an energy storage device, comprising a plurality of electrode sheets, which are assembled into a battery cell (1) in a stacking manner in which current collectors, active materials and separators are alternately stacked, the battery cell is coated with a shell, the outermost two current collectors are respectively a total positive current collector (11) and a total negative current collector (12), the inner sides of the total positive current collector (11) and the total negative current collector (12) are respectively provided with a negative electrode active material layer (14) and a positive electrode active material layer (15), the inner battery cell electrode sheet comprises an internal current collector (16), the A positive electrode active material layer (15) and a negative electrode active material layer (14), wherein the positive electrode active material layer (15) and the negative electrode active material layer (14) are respectively arranged on the two side surfaces of the internal current collector (16), and the specific arrangement method can adopt at least one of coating, adhesion, plating or doping, and at least one layer of conductive slurry coating (18) is arranged between the two outer current collectors (11, 12) and the internal current collector (16) and the positive electrode active material layer (15) and the negative electrode active material layer (14); The conductive slurry coating (18) is prepared in the following steps: Step 1: Weigh ammonium persulfate (APS) powder, add 20% paraffin and 10% emulsifier, and stir the mixture with a magnetic stirrer to obtain paraffin-coated APS suspension particles; Step 2: adding hydrogen peroxide solution to the suspension particles in step 1 to obtain hydroxylated APS, i.e. APS-OH; Step 3: Add 1 mol / L acetic acid solution to the APS-OH suspension particles obtained in step 2, disperse them evenly, react at a temperature of 10-100°C under magnetic stirring, and after the reaction is completed, dry them in a vacuum oven, grind them for later use, and the obtained product is APS-COOH; Step 4: Weigh APS-COOH particles, add acetic acid solution, ultrasonicate for 0.5h, add aniline (An) at a mass ratio of APS-COOH to aniline (An) of 1:1-1:10, ultrasonically disperse, magnetically stir, dry in a vacuum oven after the reaction is completed, grind for later use, and the obtained product is recorded as APS-An+; Step 5: Using deionized water as solvent, dispersant PVP, binder CMC and APS-An+ are completely dissolved, then graphene conductive filler is added and stirred to mix evenly, then homogenized multiple times with a homogenizer at a specific pressure, the material is discharged, and the slurry is collected after passing through a gauze, and the collected slurry is vacuum stirred and degassed to obtain a conductive slurry; Step 6: The conductive slurry obtained in step 5 is applied to the current collector by spraying or extrusion.

[0009] In a preferred embodiment of the present invention, a layer of the conductive slurry coating is coated on the surfaces of the two outer current collectors and the inner current collector.

[0010] In a preferred embodiment of the present invention, in the step 1, the emulsifier used is sorbitan fatty acid ester.

[0011] In a preferred embodiment of the present invention, in the step 1, the obtained mixture is stirred with a magnetic stirrer for 30 minutes to obtain paraffin-coated APS suspension particles.

[0012] In a preferred embodiment of the present invention, in the step three, the APS-OH suspension particles obtained in the step two are added to a 1 mol / L acetic acid solution, dispersed evenly, and reacted for 6 hours at a temperature of 70°C under magnetic stirring. After the reaction is completed, the particles are dried in a vacuum oven for 24 hours and ground for later use. The resulting product is APS-COOH.

[0013] In a preferred embodiment of the present invention, in the step 4, the mass ratio of APS-COOH to aniline (An) is 1:5.

[0014] In a preferred embodiment of the present invention, in the step 4, after adding aniline (An), ultrasonic dispersion is performed for 20 min, magnetic stirring is performed for 3 h, and after the reaction is completed, it is dried in a vacuum oven for 24 h and ground for later use. The obtained product is recorded as APS-An+.

[0015] In a preferred embodiment of the present invention, in step 5, a homogenizer is used to homogenize 6 to 12 times at a pressure of 800 to 1000 bar, and the material is discharged and collected after passing through a 150-mesh gauze. The collected slurry is vacuum stirred and degassed to obtain a conductive slurry.

[0016] In a preferred embodiment of the present invention, the positive electrode active material layer and the negative electrode active material layer are disposed on the at least one conductive slurry coating layer by coating.

[0017] In a preferred embodiment of the present invention, the positive electrode active material layer and the negative electrode active material layer are porous structures with ion channels.

[0018] Compared with the prior art, the present invention is based on reality. By setting a layer of self-limiting temperature conductive slurry between the current collector and the active material of the energy storage device, and the slurry has good conductive function at room temperature, the use of conductive carbon black is reduced, the energy density of the pole piece is improved, and the adhesive has a high bonding force with the active material layer, so as to improve the stability of the pole piece, release the expansion stress during the battery charging and discharging process, reduce the battery polarization and reduce the battery internal resistance, and improve the cycle performance. When the device temperature rises, the volume of the polymer expands, especially when the temperature rises to the melting point of the polymer, the matrix expands greatly, causing the distance of the binder to increase, and it changes from a good conductor to an insulating state, thereby cutting off the current transmission between the active materials or between the active coating and the electrode current collector, inhibiting the continuation of the electrode reaction, and providing on-site overheating protection for the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of energy storage device.

[0020] Figure 2 Schematic diagram of coating a conductive slurry layer and an active material layer on a current collector.

[0021] Figure 3 This is the preparation process of core-shell structure PTC materials.

[0022] Figure 4 This is a diagram of core-shell structure PTC material.

[0023] Figure 5 The temperature test comparison is between a common conductive paste and an energy storage device using the self-controlling temperature conductive paste of the present invention. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings so that the purpose, features and advantages of the present invention can be more clearly understood. It should be understood that the embodiments shown in the accompanying drawings are not intended to limit the scope of the present invention, but are only intended to illustrate the essential spirit of the technical solution of the present invention.

[0025] In the following description, certain specific details are set forth for the purpose of illustrating the various disclosed embodiments to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the relevant art will recognize that the embodiments may be practiced without one or more of these specific details. In other cases, well-known devices, structures, and techniques associated with the present application may not be shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.

[0026] References throughout the specification to "one embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Thus, the appearances of "in one embodiment" or "in an embodiment" in various places throughout the specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any manner in one or more embodiments.

[0027] In the following description, in order to clearly show the structure and working mode of the present invention, many directional words will be used for description, but the words "front", "back", "left", "right", "outside", "inside", "outward", "inward", "up", "down", etc. should be understood as convenient terms and should not be understood as restrictive terms.

[0028] It should be noted that the features shown in the drawings of the present application may belong to one embodiment or to different embodiments, as long as there is no conflict between these features. In order to save space, the present application may use the same drawing to illustrate different embodiments, that is, the same drawing of the present application may be used to reflect the features in different embodiments.

[0029] like Figure 1 and 2 An energy storage device 1 shown includes multiple electrode sheets, which are assembled into a battery cell 1 in an alternating stacking manner of current collectors, active materials and separators, and the battery cell is covered with a shell. The two outermost current collectors are respectively a total positive current collector 11 and a total negative current collector 12, and the inner sides of the positive current collector 11 and the total negative current collector 12 are respectively provided with a negative electrode active material layer 14 and a positive electrode active material layer 15, and the inner battery cell electrode sheet includes an inner current collector 16, a positive electrode active material layer 15 and a negative electrode active material layer 14, and the positive electrode material layer 15 and the negative electrode material layer 14 are respectively arranged on the two side surfaces of the inner current collector 16, and the specific arrangement method can adopt feasible methods such as coating, adhesion, plating or doping, and no matter whether the outer two current collectors or the inner current collector, at least one layer of conductive slurry coating 18 is arranged between them and the active material layer.

[0030] In order to reduce the volume of the entire energy storage device 1, the positive active material layer 15 and the negative active material layer 14 of the internal battery cell can be closely fitted with the diaphragm 13, thereby reducing the space occupied by multiple internal battery cell pole pieces. However, the present invention is not limited to closely fitting the internal battery cell pole pieces with the diaphragm. The position between the internal battery cell pole pieces and the diaphragm 13 can also be arranged according to the specific use environment, such as frame spacing arrangement; an internal diaphragm 13 is arranged between each positive active material layer 15 and negative active material layer 14, in order to make the internal battery cell pole pieces and the diaphragm 13 closely fit. The diaphragm 13 is one of cellulose paper, PP, PE, and ceramics, and its surface is a structure of irregularly stacked short fibers of different diameters and irregularities, presenting holes of different sizes and shapes for ion shuttle, and at the same time, the positive active material layer 15 and the negative active material layer 14 are pore structures with ion channels.

[0031] like Figure 2 As shown, the conductive slurry coating 18 is a self-limiting temperature conductive slurry coating. The conductive slurry is composed of a polymer and carbon point particles uniformly dispersed in a polymer aqueous solution. The polymer carbon points form a conductive network on the polymer molecular chain, which improves the conductive properties of the binder and can avoid the phenomenon of agglomeration due to the difficulty of dispersing the conductive agent during the slurrying process, thereby preventing the electrode from having a poor appearance during the coating process. When the device temperature rises to about 100°C, the polymer fluidity will gradually increase, and it will cover the conductive particles, destroying the original conductive network, increasing the internal resistance of the slurry, and increasing the resistance of the device by several orders of magnitude, thereby preventing the movement of ions, greatly reducing the short-circuit current, and slowing down the heat generation effect inside the device. At the same time, the conductive slurry gradually separates from the current collector, and the transmission of ions and electrons is blocked, which plays a role of high-temperature blocking, thereby protecting the safety of the device. While playing a safety role, this material can effectively protect the current collector from being corroded by the electrolyte and improve the chemical stability and thermal stability of the current collector.

[0032] The above conductive paste preparation process is as follows (eg Figure 3 shown): Step 1: Weigh ammonium persulfate (APS) powder, add 20% paraffin and 10% emulsifier, the selected emulsifier is a non-ionic surfactant, i.e. sorbitan fatty acid ester. After the mixture is stirred by a magnetic stirrer for 30 minutes, a paraffin-coated APS suspension is obtained; Step 2: Add hydrogen peroxide solution to the suspension obtained in step 1 to obtain hydroxylated APS, i.e. APS-OH; Step 3: Add 1 mol / L acetic acid solution to the APS-OH suspension particles and disperse them evenly. React for 6 h at a temperature of 10-100°C, preferably 70°C, under magnetic stirring. After the reaction is completed, dry in a vacuum oven for 24 h, grind for later use, and the resulting product is APS-COOH; Step 4: Weigh APS-COOH particles, add acetic acid solution, and ultrasonicate for 0.5h. According to the mass ratio of APS-COOH to aniline (An) of 1:1-1:10, preferably 1:5, add aniline (An), ultrasonically disperse for 20 min, and magnetically stir for 3h. After the reaction is completed, dry in a vacuum oven for 24h, grind and set aside. The obtained product is recorded as APS-An+; Step 5: Use deionized water as solvent to completely dissolve the dispersant PVP, binder CMC and APS-An+, then add the graphene conductive filler and stir to mix evenly, then use a homogenizer to homogenize 6 to 12 times at a pressure of 800 to 1000 bar, discharge the material, and collect the slurry after passing through a 150-mesh gauze. The collected slurry is vacuum stirred and degassed to obtain a conductive slurry; Step 6: The conductive slurry is applied to the current collector by spraying or extrusion; refer to Figure 4 As shown, it can be seen that the conductive paste APS has a core-shell structure. When the device temperature rises to 100°C, the APS initiator escapes from the paraffin, triggering a cross-linking reaction of APS-An+, capturing conductive particles, and the paste changes from a good conductor to an insulating state, thereby cutting off the current transmission between active materials or between the active coating and the electrode current collector, inhibiting the continuation of the electrode reaction, and providing overheating protection for the device.

[0033] like Figure 5 As shown, the self-limiting temperature conductive paste provided by the present invention has a significant jump in resistance at 60°C and above, and its resistance has increased by 6 times compared to room temperature, with excellent performance. However, the resistance of ordinary conductive paste (main components: deionized water / carbon-based conductive material / binder, without PTC material) remains stable and the resistance change is small when the temperature rises. Therefore, the self-limiting temperature conductive paste provided by the present invention has a high-temperature blocking effect.

[0034] The electrochemical test of the energy storage device 1 of the present invention is carried out in the following specific steps: 1. Capacity retention rate: At 25℃, charge to 100% SOC at 1C, then place it in 60℃ and 100℃ environment, keep it for 24 hours, take out the monomer and place it at room temperature, discharge to 0% SOC, calculate the capacity retention rate and DCR at this time; 2. The energy storage device 1 obtained above and the battery prepared in the comparative example were subjected to relevant safety tests, and the results are shown in Table 1; a. Needle puncture safety test (GB 31485-2015): Use a high temperature resistant steel needle with a diameter of φ=8mm to penetrate the battery plate at a speed of 25mm / s from a direction perpendicular to the battery plate. The battery passes if it does not catch fire or explode; b. Heating test: The temperature of the incubator is raised to 130°C at a rate of 5°C / min and maintained at this temperature for 30 minutes. The battery does not explode or catch fire.

[0035] Table 1 Experimental results of the present invention and comparative examples Analysis of experimental results: The "core-shell structure" thermally safe conductive paste provided by the present invention, when the battery is in a high-temperature thermal runaway environment, the initiator will escape from the "core", triggering a cross-linking reaction in the "shell", quickly responding to the internal resistance of lithium ions, hindering the migration of electrons and lithium ions, thereby protecting the safety of the battery. In the results of the present invention, the capacity retention rate of energy storage device 1 is higher than that of the comparative example, and the DCR at high temperature is greater than that of the comparative example. In addition, for the results of the safety test, there is no abnormality in the examples, indicating that the conductive paste can effectively protect the safety of the battery.

[0036] In this specification, the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. In particular, for the embodiments described later, the description is relatively simple, and the relevant parts can be referred to the partial description of the previous embodiments.

[0037] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. An energy storage device, characterized in that: The invention comprises a plurality of electrode sheets, which are assembled into a battery cell (1) in a stacking manner in which current collectors, active materials and separators are alternately stacked. The battery cell (1) is coated with a shell on the outside, and the two outermost current collectors are respectively a total positive current collector (11) and a total negative current collector (12). The inner sides of the total positive current collector (11) and the total negative current collector (12) are respectively provided with a negative electrode active material layer (14) and a positive electrode active material layer (15). The inner battery cell electrode sheet comprises an internal current collector (16), the positive electrode active material layer (15) and the A negative electrode active material layer (14), the positive electrode active material layer (15) and the negative electrode active material layer (14) are respectively arranged on the two side surfaces of the internal current collector (16), and the specific arrangement method can adopt at least one of coating, adhesion, plating or doping, and at least one layer of conductive slurry coating (18) is arranged between the two outer current collectors (11, 12) and the internal current collector (16) and the positive electrode active material layer (15) and the negative electrode active material layer (14); The conductive slurry coating (18) is prepared in the following steps: Step 1: Weigh ammonium persulfate (APS) powder, add 20% paraffin and 10% emulsifier, and stir the mixture with a magnetic stirrer to obtain paraffin-coated APS suspension particles; Step 2: adding hydrogen peroxide solution to the suspension particles in step 1 to obtain hydroxylated APS, i.e. APS-OH; Step 3: Add 1 mol / L acetic acid solution to the APS-OH suspension particles obtained in step 2, disperse them evenly, react at a temperature of 10-100°C under magnetic stirring, and after the reaction is completed, dry them in a vacuum oven, grind them for later use, and the obtained product is APS-COOH; Step 4: Weigh APS-COOH particles, add acetic acid solution, ultrasonicate for 0.5h, add aniline (An) at a mass ratio of APS-COOH to aniline (An) of 1:1-1:10, ultrasonically disperse, magnetically stir, dry in a vacuum oven after the reaction is completed, grind for later use, and the obtained product is recorded as APS-An+; Step 5: Using deionized water as solvent, dispersant PVP, binder CMC and APS-An+ are completely dissolved, then graphene conductive filler is added and stirred to mix evenly, then homogenized multiple times with a homogenizer at a specific pressure, the material is discharged, and the slurry is collected after passing through a gauze, and the collected slurry is vacuum stirred and degassed to obtain a conductive slurry; Step 6: The conductive slurry obtained in step 5 is applied to the current collector by spraying or extrusion.

2. The energy storage device according to claim 1, characterized in that: A layer of the conductive slurry coating (18) is coated on the surfaces of the two outer current collectors (11, 12) and the inner current collector (16).

3. The energy storage device according to claim 2, characterized in that: In the step 1, the emulsifier used is sorbitan fatty acid ester.

4. The energy storage device according to claim 3, characterized in that: In the step 1, the obtained mixture is stirred with a magnetic stirrer for 30 minutes to obtain paraffin-coated APS suspension particles.

5. The energy storage device according to claim 4, characterized in that: In the step three, the APS-OH suspension particles obtained in the step two are added to 1 mol / L acetic acid solution, dispersed evenly, reacted for 6 hours at a temperature of 70° C. under magnetic stirring, and after the reaction is completed, dried in a vacuum oven for 24 hours, ground for later use, and the obtained product is APS-COOH.

6. The energy storage device according to claim 5, characterized in that: In the step 4, the mass ratio of APS-COOH to aniline (An) is 1:

5.

7. The energy storage device according to claim 6, characterized in that: In the step 4, after adding aniline (An), ultrasonic dispersion is performed for 20 min, magnetic stirring is performed for 3 h, and after the reaction is completed, it is dried in a vacuum oven for 24 h and ground for later use. The obtained product is recorded as APS-An+.

8. The energy storage device according to claim 7, characterized in that: In the step 5, a homogenizer is used to homogenize 6 to 12 times at a pressure of 800 to 1000 bar, and the material is discharged and collected after passing through a 150-mesh gauze. The collected slurry is vacuum stirred and degassed to obtain a conductive slurry.

9. The energy storage device according to claim 1, characterized in that: The positive electrode active material layer (15) and the negative electrode active material layer (14) are disposed on the at least one conductive slurry coating layer (18) by coating.

10. The energy storage device according to claim 9, characterized in that: The positive electrode active material layer (15) and the negative electrode active material layer (14) are porous structures and have ion channels.